A Designed Zinc-finger Transcriptional Repressor of Phospholamban Improves Function of the Failing Heart - Zhang, H Steve (Nature Publishing Group, 2012)
Selective inhibition of disease-related proteins underpins the majority of successful drug–target interactions. However, development of effective antagonists is often hampered by targets that are not druggable using conventional approaches. Here, we apply engineered zinc-finger protein transcription factors (ZFP TFs) to the endogenous phospholamban (PLN) gene, which encodes a well validated but recalcitrant drug target in heart failure. We show that potent repression of PLN expression can be achieved with specificity that approaches single-gene regulation. Moreover, ZFP-driven repression of PLN increases calcium reuptake kinetics and improves contractile function of cardiac muscle both in vitro and in an animal model of heart failure. These results support the development of the PLN repressor as therapy for heart failure, and provide evidence that delivery of engineered ZFP TFs to native organs can drive therapeutically relevant levels of gene repression in vivo. Given the adaptability of designed ZFPs for binding diverse DNA sequences and the ubiquity of potential targets (promoter proximal DNA), our findings suggest that engineered ZFP repressors represent a powerful tool for the therapeutic inhibition of disease-related genes, therefore, offering the potential for therapeutic intervention in heart failure and other poorly treated human diseases.